2021
DOI: 10.1177/23409444211002210
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of their work environment, work passion, and work intentions: A replication study using three samples

Abstract: This study contributes to the emerging literature on the employee work passion appraisal (EWPA) model, by replicating structural equation modeling across three samples (total n = 4,613). We examine passion for work as a mediator of employees’ work environment characteristics and work intentions. Our data fit the structure of the EWPA model in three samples. As expected, work environment characteristics were strongly and positively correlated with harmonious passion, but contrary to our expectations, work envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
(213 reference statements)
2
8
0
Order By: Relevance
“…Third, we utilized JE as a mediator of the impact of resilience on CSAT and CPERF due to the dearth of empirical evidence in the relevant literature. Other variables such as work engagement and work passion are also critical and can also mediate the influence of resilience on the aforesaid consequences [92,93]. With this recognition, future research can incorporate both work engagement and work passion as the mediators into the model and assess whether these mediators exceed JE in explaining the linkages between resilience and job outcomes.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Third, we utilized JE as a mediator of the impact of resilience on CSAT and CPERF due to the dearth of empirical evidence in the relevant literature. Other variables such as work engagement and work passion are also critical and can also mediate the influence of resilience on the aforesaid consequences [92,93]. With this recognition, future research can incorporate both work engagement and work passion as the mediators into the model and assess whether these mediators exceed JE in explaining the linkages between resilience and job outcomes.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example, Gong et al (2018) investigated work passion among Chinese government employees and found that work passion promoted their subjective well-being and lowered their turnover intention. In addition, Peyton and Zigarmi (2021) examined the effect of work passion in large organizations in the United States, Canada, and India and found that work passion influenced various aspects of positive work behaviors such as discretionary effort, organizational citizenship behavior, and intention to stay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees' values are taken into consideration in the EWPA model, together with disposition and past events (Peyton & Zigarmi, 2021). Studies that include the passion model have demonstrated the significant role of different personal characteristics such as locus of control, motivational outlook and cynicism (Roberts & Zigarmi, 2014;Zigarmi, Galloway & Roberts, 2018).…”
Section: Individual-level Antecedents To Work Passionmentioning
confidence: 99%
“…Such mediators for the relationship between leaders' and followers' passion are considered important due to the lack of direct passion transmission from supervisor to follower (Ho, Garg & Rogelberg, 2021). Leaders' levels of passion, focus on passion, and values were also predictors of work passion (Peyton & Zigarmi, 2021;Zigarmi & Peyton, 2012). However, attributing the responsibility for work passion creation solely to leadership could present a limited view on passion creation and maintenance, given the impact of other organisational factors and the strong role of the individual in the process.…”
Section: Situation-level Antecedents To Work Passionmentioning
confidence: 99%